Effects of Concomitant Administration of Sodium Glucose Co-transporter 2 Inhibitor with Insulin on Hemoglobin A1c, Body Mass Index and Serum Lipid Profile in Japanese Type 2 Diabetic Patients - Kusunoki, Masataka; Natsume, Yukie; Miyata, Tetsuro; Tsutsumi, Kazuhiko; Oshida, Yoshiharu (Drug Research, 2018)
In patients with type 2 diabetes mellitus who show suboptimal blood glucose control under insulin therapy alone, concomitant treatment with an additional hypoglycemic agent that differs in its mechanism of action from insulin may be considered. We conducted this clinical trial to explore whether further control of increased blood glucose level can be achieved with concomitant use of sodium glucose co-transporter 2 (SGLT2) inhibitor as concomitant with other hypoglycemic therapy, as compared to SGLT2 inhibitor monotherapy, in patients with type 2 diabetes mellitus showing decrease in blood glucose level but less than the effect of insulin monotherapy and there was no significant differences. In the SGLT2 inhibitor monotherapy group, decreases of the serum hemoglobin A1c (HbA1c) level, body weight, body mass index (BMI) and serum triglyceride, and elevation of the serum high density lipoprotein cholesterol concentration were observed as compared to the baseline values. In the type 2 diabetic patients under insulin therapy who received combined insulin plus SGLT2 inhibitor therapy, however decreases in the body weight and BMI, with only a tendency towards decrease of the serum HbA1c value, not reaching statistical significance, were observed. The combined therapy group also showed no appreciable changes of the serum triglyceride level, while the serum adiponectin level increased. The present study data indicate that combined insulin plus SGLT2 inhibitor treatment failed to afford any further improvement of the blood glucose control, as compared to SGLT2 monotherapy, in Japanese type 2 diabetic patients.
Keywords: SGLT2 inhibitor; insulin therapy; glycemic control; Japanese type 2 diabetic patients